The Effectiveness of The Implementation of Patient Safety Targets (SKP) Regarding Correctly Identifying Patients at Klungkung Area General Hospitals - Luh Putu Henny Saraswastini; Ni Nengah Adiyaryani; Kadek Sri Wahyuni Dewi (Jurnal Health Sains, 2024)
Patient safety is an important thing in the handling of patients by medical personnel in carrying out treatment, it has a very important element so that the government has established various laws and regulations relating to health in Indonesia, one of which is regarding Patient Safety Targets (SKP) which are divided into points. -points regarding targets that must be carried out by medical personnel in carrying out actions in treating patients. The aim of this study is to find out and analyze the effectiveness of implementing Patient Safety Targets (SKP) regarding the accuracy of patient identification at the Klungkung Regional General Hospital as well as knowing and analyzing related facts -Inhibiting factors in implementing Patient Safety Targets (SKP) regarding accurate patient identification at the Klungkung Regional General Hospital. The research method used in this research is an empirical legal research method with data collection techniques, namely document study techniques and interview techniques. The results of the study show that the effectiveness of implementing Patient Safety Targets (SKP) regarding the accuracy of patient identification at the Klungkung Regional General Hospital has not been achieved optimally. This is due to several inhibiting factors, namely the first is that the room conditions are not conducive, the room situation is sometimes too busy, this causes medical officers to have to serve patients quickly, with the number of patients not being comparable to the number of officers, secondly there is an assumption regarding the accuracy of the patient's identity,  what is meant in this case is that medical officers are said to feel that they already know the patient's identity, because they have been treated or met. patient for a certain period of time or repeatedly in the same room so that this assumption arises. The third monitoring factor explained in its implementation is the absence of assessment/supervision of procedures for implementing accurate patient identification, so that officers are often negligent or do not get used to identifying patients correctly.